2015
DOI: 10.1038/nature14346
|View full text |Cite
|
Sign up to set email alerts
|

Primary transcripts of microRNAs encode regulatory peptides

Abstract: MicroRNAs (miRNAs) are small regulatory RNA molecules that inhibit the expression of specific target genes by binding to and cleaving their messenger RNAs or otherwise inhibiting their translation into proteins. miRNAs are transcribed as much larger primary transcripts (pri-miRNAs), the function of which is not fully understood. Here we show that plant pri-miRNAs contain short open reading frame sequences that encode regulatory peptides. The pri-miR171b of Medicago truncatula and the pri-miR165a of Arabidopsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
344
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(357 citation statements)
references
References 13 publications
11
344
0
2
Order By: Relevance
“…1C) (Ambros, 2004;Bartel, 2004;Lauressergues et al, 2015). These RNA molecules are generated in both animals and plants by the same enzyme, RNA polymerase II (RNAPII), that mediates the synthesis of protein-coding mRNAs, and they are modified with a 5' cap and 3' polyadenylate tail.…”
Section: Introductionmentioning
confidence: 99%
“…1C) (Ambros, 2004;Bartel, 2004;Lauressergues et al, 2015). These RNA molecules are generated in both animals and plants by the same enzyme, RNA polymerase II (RNAPII), that mediates the synthesis of protein-coding mRNAs, and they are modified with a 5' cap and 3' polyadenylate tail.…”
Section: Introductionmentioning
confidence: 99%
“…Although their biogenesis and action modes have been well depicted, 8,9 new features are being uncovered and added onto the miRNAs encoded by the precursors encompassing stem-loop structures. 10,11 Research on the discovery and the regulatory activities of the miRNA species will be greatly accelerated by integrative use of diverse sequencing approaches developed from HTS platform. In this review, we introduced several HTS methods valuable for plant miRNA studies, including RNA-seq, RNA-PET-seq, sRNA-seq, dsRNA-seq, ssRNA-seq and degradome-seq.…”
Section: Discussionmentioning
confidence: 99%
“…By increasing the transcription of the primiRNAs, the miRNA-encoded peptides (miPEPs) enhance the accumulation of the corresponding mature miRNAs, resulting in the down-regulation of the target genes. 10 Thus, the above discovery refreshed our traditional view that the "junk" regions of the miRNA precursors could play a coding role. 11 Considering the sequence features of the miRNAs, and the huge sRNA population existing in plants, 12 high-throughput approaches are desired for cloning, characterization and quantification of the miRNA genes.…”
Section: Microrna Genes In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary transcripts of MIRNA genes have been thought to be localized mainly in nucleus and are processed by DCL1. Recently, Lauressergues and co-authors 12 reported that some MIRNA primary transcripts encode short peptides, call miPEPs, and that these miPEPs have a role in enhancing transcription of their own primary transcripts. They also showed that the pri-miR165a is predicted to be translated into miPEP165a, which is composed of 18 amino acid residues, proposing that the pri-miR165a is exported form nucleus to cytoplasm.…”
mentioning
confidence: 99%